Energy storage bearing material and preparation method thereof, and structural electrode and preparation method and application thereof
By using structural electrodes prepared by industrial by-products and magnetically modified soil in green energy buildings, the problems of traditional electrodes' low load-bearing capacity and cycle retention rate are solved, and efficient energy storage and environmentally friendly and sustainable development are achieved.
Patent Information
- Application Number
- CN202411433375.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional structural electrodes lack load-bearing capacity and high cycle retention rates in green energy buildings and energy self-sufficiency buildings, and there are low cycle retention rates and potential environmental risks of electrodes.
Energy storage bearing materials including industrial by-products, magnetically modified soil and conductive materials are used to form a solid three-dimensional network structure and a continuous conductive network through vibration and maintenance in the applied magnetic field to improve the bearing and conductive properties of the materials.
The high cycle retention rate (over 93%) and compressive strength of energy storage bearing materials and structural electrodes are achieved, ensuring the energy self-sufficiency and environmentally friendly and sustainable development of the building.
Smart Images

Figure CN119252668A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of resource recycling, and specifically relates to an energy storage bearing material and a preparation method thereof, as well as a structural electrode and a preparation method and application thereof. Background Art
[0002] Traditional power supply methods, such as thermal power, long-distance power transmission and distributed power generation systems, have problems in environmental protection, resource depletion, stability or land supply to varying degrees, making it difficult for traditional power supply methods to achieve sustainable development. Therefore, researchers advocate the development of green energy buildings and energy self-sufficient buildings. At present, some researchers have proposed a concept: transforming the building itself into an energy storage device and installing photovoltaic panels on the roof of the building. The electricity converted by the photovoltaic panels is directly stored in the building. The stored electricity can be used for daily electricity needs or as an emergency backup energy source to achieve energy self-sufficiency of the building.
[0003] The construction of green energy buildings and energy self-sufficient buildings naturally requires the use of structural electrodes. Traditional electrodes are usually made of metals or metal oxides and usually do not have load-bearing capacity. Some researchers have tried to use cement as a structural electrode. Although some performance has met the requirements, the cycle retention rate of the electrode is low and cannot meet the requirements of green energy buildings and energy self-sufficient buildings. Summary of the invention
[0004] The purpose of the present invention is to provide an energy storage carrying material and a preparation method thereof, as well as a structural electrode and a preparation method and application thereof. The structural electrode provided by the present invention has carrying capacity and energy storage capacity, and has a high cycle retention rate.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides an energy storage carrying material, which comprises a matrix and a conductive network structure distributed inside the matrix; the matrix is a hydration product of industrial by-products; and the conductive network structure comprises a conductive material and magnetic modified soil.
[0007] Preferably, the mass ratio of the matrix to the conductive network structure is 35-100:0.01-5; the mass ratio of the conductive material to the magnetic modified soil is 0.01-5:20-50.
[0008] The present invention also provides a method for preparing the energy storage carrying material described in the above scheme, comprising the following steps:
[0009] The industrial by-product, magnetic modified soil, conductive material and alkaline activator are mixed to obtain a mixed slurry; the industrial by-product has pozzolanic activity and can undergo a pozzolanic reaction under a pH ≥ 10 environment;
[0010] The mixed slurry is vibrated and cured in sequence in an external magnetic field to obtain the energy storage bearing material.
[0011] Preferably, the magnetic modified soil is magnetic modified clay; the preparation method of the magnetic modified clay is: mixing the activated clay with water to obtain a clay suspension, adding Fe3O4 magnetic nanoparticles to the clay suspension and stirring and mixing, so that the clay particles in the clay suspension adsorb the Fe3O4 magnetic nanoparticles; the Fe3O4 magnetic nanoparticles are composed of Fe 3+ and Fe 2+ The salts were synthesized by chemical co-precipitation.
[0012] The present invention also provides a structural electrode, comprising an electrode body and a current collector partially embedded in the electrode body; the electrode body is the energy storage carrying material described in the above scheme or the energy storage carrying material obtained by the preparation method described in the above scheme.
[0013] Preferably, the length of the electrode body connection parts on both sides of the current collector is the same as that of the electrode body, and the width is 0.3-0.7 cm.
[0014] The present invention also provides a method for preparing the structured electrode described in the above scheme, comprising the following steps:
[0015] The industrial byproduct, magnetic modified soil, conductive material and alkaline activator are mixed to obtain a mixed slurry;
[0016] The mixed slurry is injected into a mold, and a current collector is placed into the mixed slurry while the mixed slurry is in a flowing state. The mold is then vibrated and cured in an external magnetic field to obtain the structured electrode.
[0017] Preferably, the curing includes sequentially performing mold curing and demoulding curing; the temperature of the mold curing is 18-22° C., the humidity is 95-98%, and the curing time is 24-48 hours.
[0018] Preferably, the demoulding curing is carried out by immersion curing in an immersion liquid; the concentration of the immersion liquid is 1 to 6M; the immersion liquid includes one or more of NaCl solution, KCl solution, Na2SO4 solution, K2SO4 solution, NaOH solution and KOH solution; the temperature of the demoulding curing is room temperature.
[0019] The present invention also provides the application of the structured electrode described in the above scheme or the structured electrode obtained by the preparation method described in the above scheme in the field of energy development and utilization.
[0020] The present invention provides an energy storage bearing material. The energy storage bearing material provided by the present invention has good bearing capacity and energy storage capacity, high cycle retention rate, the cycle retention rate is above 93% after 5000 cycles, and high compressive strength.
[0021] The present invention also provides a method for preparing the energy storage carrying material described in the above scheme. The present invention uses industrial by-products, magnetic modified soil and conductive materials as main raw materials, wherein the industrial by-products have volcanic ash activity, and the generated hydration products form a solid three-dimensional network structure, providing the material with carrying capacity; the magnetic modified soil is oriented under the action of an external magnetic field to form a continuous conductive network, providing a path for the conductive material to form a complete conductive network; at the same time, the surface of the magnetic modified soil carries a negative charge, which makes it easy to disperse in water and combine with cations, thereby facilitating the conduction of ions or electrons and improving its electrochemical properties; the negative charge on the surface of the magnetic modified soil can also increase the dispersibility of the conductive material, overcome the characteristic of the conductive material being easy to agglomerate, and the uniformly dispersed conductive material can form more effective conductive paths and enhance the conductive properties of the material.
[0022] The present invention also provides a structural electrode. The structural electrode provided by the present invention has both load-bearing capacity and energy storage capacity, a high cycle retention rate, a cycle retention rate of more than 93% after 5,000 cycles, high compressive strength, good stability, and good compatibility with buildings. The structural electrode provided by the present invention uses the principle of double-layer capacitors to store electricity, and has good stability and durability; at the same time, it can avoid the hidden dangers of leakage and fire of traditional pseudocapacitors, as well as the disposal problems caused by the scrapping of chemical batteries, and is environmentally friendly and sustainable.
[0023] The present invention also provides a method for preparing the structured electrode described in the above scheme. The present invention uses industrial by-products, magnetic modified soil and conductive materials as main raw materials, and avoids the high energy density firing process through mixing, curing and soaking to prepare the structured electrode. Among them, the industrial by-products have volcanic ash activity, and the generated hydration products form a solid three-dimensional network structure, which can provide bearing capacity for the structured electrode; the magnetic modified soil is arranged in a directional manner under the action of an external magnetic field to form a continuous conductive network, providing a path for the conductive material to form a complete conductive network, which is conducive to the uniform transfer of electrons to every corner of the electrode through the current collector; at the same time, the surface of the magnetic modified soil carries a negative charge, which makes it easy to disperse in water and combine with cations, thereby facilitating the conduction of ions or electrons and improving its electrochemical performance; the negative charge on the surface of the magnetic modified soil can also increase the dispersibility of the conductive material, overcome the characteristic of easy agglomeration of the conductive material, and the uniformly dispersed conductive material can form more effective conductive paths, thereby enhancing the conductive performance of the structured electrode, as shown in the following example. Figure 2 shown.
[0024] The preparation method provided by the present invention has simple steps, low process energy consumption, low raw material cost, realizes resource and high-value utilization of industrial solid waste, and creates significant economic, environmental and social benefits.
[0025] The present invention also provides the application of the structured electrode described in the above scheme or the structured electrode obtained by the preparation method described in the above scheme in the field of energy development and utilization. The structured electrode provided by the present invention can be used in the field of energy development and utilization, specifically energy utilization in the field of construction or energy utilization in the field of civil engineering, such as the foundation or partition wall of a building, to support the energy self-sufficiency of the building, promote the development of green energy buildings and energy self-sufficient buildings, and has a high market promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The process flow chart of the magnetic modified soil (a) and the structured electrode (b) in the present invention;
[0028] Figure 2 A schematic diagram of the working of the structured electrode provided by the present invention;
[0029] Figure 3 The EIS curves of the structured electrodes of Example 1 and Comparative Examples 1 to 3;
[0030] Figure 4 The compressive strength diagram of the structured electrodes of Example 1 and Comparative Examples 1 to 3;
[0031] Figure 5 The surface capacitance of the structured electrodes of Example 1 and Comparative Examples 1 to 3;
[0032] Figure 6 It is the cycle retention rate of the structured electrode of Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0033] The present invention provides an energy storage carrying material, which comprises a matrix and a conductive network structure distributed inside the matrix; the matrix is a hydration product of industrial by-products; and the conductive network structure comprises a conductive material and magnetic modified soil.
[0034] In the present invention, the mass ratio of the matrix and the conductive network structure is preferably 35-100:0.01-5, specifically 35:0.01, 35:0.1, 35:1, 35:5, 95:0.01, 95:0.1, 95:1, 95:5, 100:0.01, 100:0.1, 100:1 or 100:5.
[0035] In the present invention, the mass ratio of the conductive material to the magnetic modified soil is preferably 0.01-5:20-50, specifically 0.01:20, 0.01:30, 0.01:40, 0.01:50, 0.1:20, 0.1:30, 0.1:40, 0.1:50, 1:20, 1:30, 1:40, 1:50, 3:20, 3:40, 5:20 or 5:50.
[0036] The present invention also provides a method for preparing the energy storage carrying material described in the above scheme, comprising the following steps:
[0037] Mixing industrial by-products, magnetic modified soil, conductive materials and alkaline activators to obtain a mixed slurry; the industrial by-products have pozzolanic activity and can undergo a pozzolanic reaction under a pH ≥ 10 environment;
[0038] The mixed slurry is vibrated and cured in sequence in an external magnetic field to obtain the energy storage bearing material.
[0039] The present invention mixes industrial by-products, magnetic modified soil, conductive materials and alkaline activators to obtain a mixed slurry. In the present invention, the industrial by-products preferably include one or more of silicon-aluminum-based by-products, calcium sulfate-based by-products and alkaline by-products; the silicon-aluminum-based by-products preferably include one or more of slag, steel slag and fly ash; the calcium sulfate-based by-products preferably include one or more of phosphogypsum, fluorite and citric acid gypsum; the alkaline by-products preferably include one or more of carbide slag and alkaline slag.
[0040] Industrial by-products usually contain metal impurities and metal oxides, which not only improve the conductivity of the gelling material, but also form a conductive network during the alkali excitation process, thereby improving the overall conductivity of the material. In addition, industrial by-products are produced along with the main products, and there is no additional carbon emission, which makes the energy storage material of the present invention have the characteristics of low economic cost, low environmental cost and high value of solid waste utilization.
[0041] In the present invention, the particle size of the industrial by-product is preferably less than or equal to 0.15 micrometers, specifically 0.15 micrometers, 0.13 micrometers, 0.11 micrometers, 0.10 micrometers, 0.08 micrometers, 0.05 micrometers, 0.03 micrometers or 0.01 micrometers.
[0042] In the present invention, the industrial by-products are preferably pretreated before use; the pretreatment is preferably: drying, grinding and sieving the industrial by-products in sequence; the drying is preferably oven drying; the drying temperature is preferably 40 to 105°C, and preferably the mass change is no more than 0.5% within 24 hours.
[0043] In the present invention, when the industrial by-product is a silicon-aluminum based by-product, the drying temperature is preferably 80-105°C, specifically 80°C, 85°C, 90°C, 95°C, 100°C or 105°C; when the industrial by-product is a calcium sulfate based by-product, the drying temperature is preferably 45-60°C, specifically 45°C, 50°C, 55°C or 60°C; when the industrial by-product is an alkaline by-product, the drying temperature is preferably 40-60°C, specifically 40°C, 45°C, 50°C, 55°C or 60°C.
[0044] In the present invention, the grinding time is preferably 10 to 15 minutes, specifically 10 minutes, 12 minutes, 14 minutes or 15 minutes.
[0045] In the present invention, the sieved particle size is preferably the target particle size of industrial by-products, and the sieve residue is preferably controlled to be less than 5%.
[0046] In the present invention, the magnetic modified soil is preferably magnetic modified clay; the preparation method of the magnetic modified clay is preferably: mixing the activated clay with water (referred to as the second mixing) to obtain a clay suspension, adding Fe3O4 magnetic nanoparticles to the clay suspension and stirring and mixing (referred to as the third mixing), so that the clay particles in the clay suspension adsorb the Fe3O4 magnetic nanoparticles.
[0047] In the present invention, the water is preferably deionized water; the clay is preferably a natural clay mineral with a liquid limit of 27-40% and a plastic limit of 20-27%, and specifically may be one or more of silty clay, silty clay and kaolin.
[0048] In clay, high-valent atoms are usually isostructurally replaced by low-valent atoms (octahedral atoms Al or Mg are replaced by Li). The isostructural substitution causes the clay surface to have a negative charge, which is compensated by interlayer cations (such as Li, Na and Ca). These characteristics are beneficial to clay modification.
[0049] In the present invention, the clay is preferably dried and then ground before use; the drying equipment is preferably an oven; the drying temperature is preferably 105° C., and the insulation time is preferably not less than 24 hours, specifically 24 hours, 30 hours, 36 hours or 48 hours; the grinding equipment is preferably a ball mill; the grinding speed is preferably 16 to 20 rpm, specifically 16 rpm, 17 rpm, 18 rpm, 19 rpm or 20 rpm, and the grinding time is preferably 15 to 30 minutes, specifically 15 minutes, 18 minutes, 24 minutes, 27 minutes or 30 minutes.
[0050] In the present invention, the activation is preferably hydrochloric acid activation; the hydrochloric acid activation is preferably: mixing clay and hydrochloric acid (referred to as mixed B) for activation and then letting stand; the mass ratio of clay to hydrochloric acid is preferably 1:30-50, specifically 1:30, 1:35, 1:40, 1:45 or 1:50; the concentration of hydrochloric acid is preferably 3.5-4.5M, specifically 3.5M, 4.0M or 4.5M; the mixed B is preferably stirred and mixed; the standing time is preferably 1h.
[0051] In the present invention, after the standing, the system is preferably further subjected to the steps of removing the supernatant, washing and centrifuging, and drying in sequence; the washing and centrifuging is preferably performed 2 to 5 times, specifically 2, 3, 4 or 5 times, until the pH value of the supernatant is 6.1 to 6.9; the water used for washing and centrifuging is preferably deionized water;
[0052] In the present invention, the drying equipment is preferably an oven; the drying temperature is preferably 50-60°C, specifically 50°C, 53°C, 56°C or 60°C, and the insulation time is preferably 24h.
[0053] In the present invention, the mass ratio of the activated clay to water is preferably 1:5-10, specifically 1:5.2, 1:6.4, 1:7.6 or 1:10.
[0054] In the present invention, the temperature of the second mixing is preferably not more than 60°C, specifically room temperature, 40°C, 50°C or 60°C; the second mixing is preferably stirring mixing, more preferably ultrasound-assisted stirring mixing; the frequency of the ultrasound is preferably 40-60kHz, specifically 40kHz, 50kHz or 60kHz, and the ultrasound time is preferably 15-30min, specifically 15min, 20min, 25min or 30min.
[0055] In the present invention, the mass ratio of the activated clay to the Fe3O4 magnetic nanoparticles is preferably 1:0.5-0.7, specifically 1:0.5, 1:0.63, 1:0.67 or 1:0.7.
[0056] In the present invention, the Fe3O4 magnetic nanoparticles are preferably made of Fe 3+ and Fe 2+ The salts were synthesized by chemical co-precipitation.
[0057] In the present invention, the method for preparing the Fe3O4 magnetic nanoparticles is preferably as follows: a trivalent iron salt, a divalent iron salt, a pH regulator and water are mixed (referred to as the first mixing to obtain a mixed solution) for coprecipitation reaction to obtain Fe3O4 magnetic nanoparticles (specifically, Figure 1 (shown in a).
[0058] In the present invention, the pH adjuster preferably includes one or both of NaOH and NH4OH; and the water is preferably deionized water.
[0059] In the present invention, the molar ratio of the ferric iron salt to the ferrous iron salt is preferably 1.8-1:2.2-1, specifically 2:1; the concentration of the ferric iron salt in the mixed solution is preferably 0.1-1M, specifically 0.5M; the amount of the pH regulator added is preferably based on the pH value of the mixed solution to 9-11.
[0060] In the present invention, the first mixing is preferably: dissolving a ferric salt in water (referred to as the first dissolution) to obtain a ferric salt solution, dissolving a ferrous salt in water (referred to as the second dissolution) to obtain a ferrous salt solution, mixing the ferric salt solution and the ferrous salt solution (referred to as mixing A) to obtain an iron salt solution, and then dripping a pH regulator into the iron salt solution while stirring.
[0061] In the present invention, when bubbles appear during the first dissolution or the second dissolution, the solution is preferably allowed to stand for 5 to 10 minutes, specifically 5 minutes, 7 minutes, 9 minutes or 10 minutes. The bubbles in the ferric salt solution or the ferrous salt solution are dissipated by standing.
[0062] In the present invention, the temperature of the first dissolution or the second dissolution is preferably 40-60° C., specifically 40° C., 45° C., 50° C., 55° C. or 60° C. The present invention accelerates the dissolution of the ferric salt and the ferrous salt by heating to obtain a uniform solution.
[0063] In the present invention, the mixing A is preferably stirred and mixed; the stirring and mixing time is preferably no more than 3 minutes, specifically 1 minute, 2 minutes or 3 minutes. The present invention prevents Fe 2+ Oxidized to Fe by oxygen in the air 3+ .
[0064] In the present invention, the temperature of the stirring and dropping is preferably room temperature; the stirring and dropping is preferably dropped while magnetic stirring; the rotation speed of the magnetic stirring is preferably 300-600rpm, specifically 300rpm, 400rpm, 500rpm or 600rpm; the dropping rate is preferably 0.5-1.0 drops / second, specifically 0.5 drops / second, 0.7 drops / second, 0.9 drops / second or 1.0 drops / second, and the dropping time is preferably not more than 30min, specifically 10min, 15min, 20min, 25min or 30min.
[0065] In the present invention, the coprecipitation reaction is preferably carried out under stirring conditions; the stirring speed is preferably 400-800rpm, specifically 400rpm, 500rpm, 600rpm, 700rpm or 800rpm; the coprecipitation reaction temperature is preferably room temperature, and the reaction time is preferably 30-60min, specifically 30min, 40min, 50min or 60min.
[0066] In the present invention, after the coprecipitation reaction, the obtained system is preferably subjected to solid-liquid separation, purification and drying in sequence; the purification is preferably performed more than once, specifically, once, twice, three times or four times.
[0067] In the present invention, the solid-liquid separation is preferably centrifugal; the centrifugal speed is preferably 7000-9000 rpm, specifically 7000 rpm, 8000 rpm or 9000 rpm, and the centrifugal time is preferably 10-20 min, specifically 10 min, 15 min or 20 min. The present invention separates the Fe3O4 magnetic nanoparticles from the solution by solid-liquid separation to precipitate the Fe3O4 magnetic nanoparticles to the bottom of the tube.
[0068] In the present invention, the purification is preferably performed in sequence by redispersion of the precipitate and solid-liquid separation again; the redispersion of the precipitate is preferably: ultrasonic mixing of the precipitate and the dispersion solvent; the dispersion solvent is preferably deionized water or ethanol; the volume ratio of the precipitate to the dispersion solvent is preferably 2 to 5:1, specifically 2:1, 3:1, 4:1 or 5:1; the ultrasonic mixing time is preferably 15 to 30 minutes, specifically 15 minutes, 20 minutes, 25 minutes, 30 minutes or 18 minutes. The present invention helps the dispersion of the precipitate by ultrasound.
[0069] In the present invention, the parameters of the second solid-liquid separation are preferably the same as those of the solid-liquid separation, and will not be described in detail herein.
[0070] In the present invention, the drying equipment is preferably an oven; the drying temperature is preferably 40-60°C, specifically 40°C, 45°C, 50°C, 55°C or 60°C, preferably until the mass change is less than 0.1% within 24 hours.
[0071] In the present invention, the temperature of the third mixing is preferably not more than 60°C, specifically room temperature, 40°C, 50°C or 60°C; the rotation speed of the third mixing is preferably 400-800rpm, specifically 400rpm, 500rpm, 600rpm, 700rpm or 800rpm, and the mixing time is preferably 30-60min, specifically 30min, 40min, 50min or 60min; the third mixing is preferably carried out under ultrasonic-assisted conditions; the frequency of the ultrasound is preferably 40-60kHz, specifically 40kHz, 50kHz or 60kHz.
[0072] In the present invention, the third mixing preferably further comprises sequentially solid-liquid separation, water washing and drying of the obtained system; the solid-liquid separation is preferably centrifugal separation and magnetic separation.
[0073] In the present invention, the rotation speed of the centrifugal separation is preferably 7000-9000 rpm, and the centrifugal time is preferably 10-20 min. In the present invention, the magnetic modified soil is precipitated to the bottom of the tube by centrifugal separation, and the supernatant is removed to obtain the magnetic modified soil precipitate.
[0074] In the present invention, the magnetic separation is preferably performed by placing a magnet at the bottom of a container containing the system, so that all the magnetically modified soil is gathered at the bottom of the container, and the supernatant is poured out.
[0075] In the present invention, the water used for washing is preferably deionized water; the number of times of washing is preferably more than 3 times; the drying equipment is preferably a vacuum dryer; the drying temperature is preferably 45-55°C, specifically 45°C, 50°C or 55°C, and the insulation time is preferably 24h.
[0076] In the present invention, the raw material of the magnetic modified soil preferably also includes a dispersant; the dispersant preferably includes one or more of polyvinyl alcohol (PVA), sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB); the mass ratio of the dispersant to the Fe3O4 magnetic nanoparticles is preferably 3 to 1:1, specifically 1:1; the present invention prevents the aggregation of Fe3O4 magnetic nanoparticles by adding a dispersant. The present invention prepares the magnetic modified soil by introducing the Fe3O4 magnetic nanoparticles into the nanopores of the clay.
[0077] In the present invention, the mass ratio of the industrial by-product to the magnetic modified soil is preferably 30-80:20-50, specifically 30:20, 40:50, 80:20, 70:30, 60:40, 50:30, 50:40 or 50:50.
[0078] In the present invention, the conductive material preferably includes one or more of graphene, carbon black and carbon nanotubes; the particle size of the conductive material is preferably 9 to 20 microns, specifically 9 microns, 11 microns, 13 microns, 15 microns, 17 microns or 20 microns.
[0079] In the present invention, the mass ratio of the industrial by-product to the conductive material is preferably 30-80:0.01-5.00, specifically 30:0.01, 30:0.1, 30:1, 30:3, 30:5, 50:0.1, 60:1, 70:3, 40:4 or 80:0.01.
[0080] In the present invention, the alkali activator preferably includes one or more of a water-soluble alkali activator and a non-water-soluble alkali activator; the water-soluble alkali activator preferably includes one or more of industrial alkali, sodium carbonate or potassium alkali; the sodium carbonate is preferably a sodium silicate solution; the non-water-soluble alkali activator preferably includes one or more of quicklime, carbide slag, limestone waste slag and alkali slag; the modulus of the water-soluble alkali activator is preferably designed according to the strength of industrial by-products, which can be 2.3, 2.4 or 3.3, preferably 3.3, and the Baume degree is preferably 30-50°Bé. The present invention adopts the above-mentioned alkali activator to avoid the dispersant from losing its function in alkaline solution caused by alkali activators such as NaOH and KOH, thereby ensuring the dispersion effect of the conductive material.
[0081] In the present invention, the mass ratio of the industrial by-product to the alkaline activator is preferably 30-80:5-20, specifically 30:5, 30:10, 30:15, 30:20, 55:5, 40:10, 70:15, 60:20 or 80:5.
[0082] In the present invention, when the alkali activator is a water-soluble alkali activator, the mixing of the industrial by-products, magnetic modified soil, conductive material and alkali activator is preferably: premixing the industrial by-products, magnetic modified soil and conductive material (referred to as the first premixing) to obtain a premix, premixing the water-soluble alkali activator and water (referred to as the second premixing) to obtain a water-soluble alkali activator solution, and then mixing the premix and the water-soluble alkali activator solution (referred to as the fourth mixing).
[0083] In the present invention, the first premixing device is preferably a planetary ball mill; the first premixing is preferably stirring mixing; the stirring mixing speed is preferably 100-200rpm, specifically 100rpm, 140rpm, 170rpm or 200rpm, and the mixing time is preferably 10-30s, specifically 10s, 15s, 20s, 25s or 30s.
[0084] In the present invention, the water is preferably deionized water; the ratio of the mass of the water to the total mass of the industrial by-products, magnetic modified soil and alkaline activator is preferably 0.50 to 0.65:1, specifically 0.50:1, 0.55:1, 0.60:1 or 0.65:1.
[0085] In the present invention, the second premixing is preferably performed by stirring and mixing.
[0086] In the present invention, the fourth mixing is preferably stirring mixing; the rotation speed of the stirring mixing is preferably 600-800rpm, specifically 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, and the mixing time is preferably 3-5min, specifically 3min, 4min or 5min.
[0087] In the present invention, when the alkali activator is a water-insoluble alkali activator, the mixing of the industrial by-products, magnetic modified soil, conductive material and alkali activator is preferably: premixing the alkali activator with the industrial by-products, magnetic modified soil and conductive material (referred to as the third premixing) to obtain a premix, and then mixing the premix with water (referred to as the fifth mixing).
[0088] In the present invention, the equipment for the third premixing is preferably a planetary ball mill; the third premixing is preferably stirring and mixing; the rotation speed of the stirring and mixing is preferably 100-200rpm, specifically 100rpm, 140rpm, 170rpm or 200rpm, and the mixing time is preferably 10-30s, specifically 10s, 15s, 20s, 25s or 30s.
[0089] In the present invention, the water is preferably deionized water; the ratio of the mass of the water to the total mass of the industrial by-products, magnetic modified soil and alkaline activator is preferably 0.50 to 0.65:1, specifically 0.50:1, 0.55:1, 0.60:1 or 0.65:1.
[0090] In the present invention, the fifth mixing is preferably stirring mixing; the stirring mixing speed is preferably 600-800rpm, specifically 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, and the mixing time is preferably 3-5min, specifically 3min, 4min or 5min.
[0091] In the present invention, the raw materials of the mixed slurry preferably also include a water reducer; the water reducer is preferably one or more of a polycarboxylate high-efficiency water reducer (PCE) and a naphthalene-based water reducer (NS); the present invention selectively adds a water reducer according to industrial by-products from different sources to further optimize the fluidity of the slurry and facilitate injection molding.
[0092] After obtaining the mixed slurry, the present invention sequentially compacts and cures the mixed slurry in an external magnetic field to obtain the energy storage bearing material.
[0093] In the present invention, the external magnetic field is preferably provided by a magnet; the magnetic field strength of the external magnetic field is preferably 0.01-0.5T, specifically 0.01T, 0.05T, 0.1T, 0.3T or 0.5T; the size of the magnet is preferably not less than the bottom size of the mold. The present invention uses an external magnetic field of the above strength to ensure that the magnetic modified soil is oriented under the action of the magnetic field, and at the same time, the magnetic interaction force is weak, which can reduce the agglomeration of particles.
[0094] In the present invention, the compaction device is preferably a vibration table; the compaction time is preferably 3 to 5 minutes, specifically 3 minutes, 4 minutes or 5 minutes.
[0095] In the present invention, the curing preferably includes performing mold curing and demolding curing in sequence; the temperature of the mold curing is preferably 18-22°C, the humidity is preferably 95-98%, and the curing time is preferably 24-48h (the curing time is calculated from the completion of vibration).
[0096] In the present invention, the demoulding curing is preferably performed by soaking in a soaking liquid; the concentration of the soaking liquid is preferably 1 to 6M, specifically 1M, 3M, 5M or 6M; the soaking liquid preferably includes one or more of NaCl solution, KCl solution, Na2SO4 solution, K2SO4 solution, NaOH solution and KOH solution; the temperature of the demoulding curing is preferably room temperature. The present invention achieves better capacitance performance through soaking curing.
[0097] The present invention also provides a structural electrode, comprising an electrode body and a current collector partially embedded in the electrode body; the electrode body is the energy storage carrying material described in the above scheme or the energy storage carrying material obtained by the preparation method described in the above scheme.
[0098] The structural electrode provided by the present invention includes an electrode body; the aspect ratio of the electrode body is preferably 1:1-5, specifically 1:1, 1:2, 1:3, 1:4 or 1:5, and the aspect ratio is preferably 1:0.075-1, specifically 1:0.075, 1:0.1, 1:0.4, 1:0.7 or 1:1; the electrode body is the energy storage carrying material described in the above scheme or the energy storage carrying material obtained by the preparation method described in the above scheme.
[0099] The structural electrode provided by the present invention includes a current collector; the current collector is preferably foam metal, conductive fiber, carbon cloth carbon paper or stainless steel; the foam metal is preferably foam nickel; the size of the current collector is smaller than the electrode body; the length and width of the current collector are independently preferably 75-90% of the corresponding length and width of the electrode body, specifically 75%, 80%, 85% or 90%. The size of the current collector of the present invention is smaller than the electrode body, which can avoid the structural electrode from breaking.
[0100] In the present invention, the length of the electrode body connection part on both sides of the current collector is preferably the same as that of the electrode body, and the width is preferably 0.3-0.7 cm, specifically 0.3 cm, 0.4 cm, 0.5 cm, 0.6 cm or 0.7 cm.
[0101] The structural electrode provided by the present invention has a strength of more than 10 MPa after curing for 7 days.
[0102] The present invention also provides a method for preparing the structured electrode described in the above scheme, comprising the following steps:
[0103] The industrial byproduct, magnetic modified soil, conductive material and alkaline activator are mixed to obtain a mixed slurry;
[0104] The mixed slurry is injected into a mold, and a current collector is placed into the mixed slurry while the mixed slurry is in a flowing state. Then, the mold is vibrated and cured in an external magnetic field to obtain the structured electrode (specifically, Figure 1 (as shown in b).
[0105] The present invention mixes industrial byproducts, magnetic modified soil, conductive materials and alkaline activators to obtain a mixed slurry. In the present invention, the preparation method of the mixed slurry is preferably the same as the above scheme, which will not be repeated here.
[0106] After obtaining the mixed slurry, the present invention injects the mixed slurry into a mold, immerses the current collector into the mixed slurry while the mixed slurry is in a flowing state, and then successively vibrates and cures the mold in an external magnetic field to obtain the structural electrode. The present invention has no special requirements for the specific type of the mold, as long as the size of the mold can meet the size of the above-mentioned electrode body. In a specific embodiment of the present invention, the mold is preferably an iron mold, a polyethylene mold or a silicone mold.
[0107] In the present invention, the distance between the edge of the current collector and the edge of the mold is preferably 0.3-0.7 cm, specifically 0.3 cm, 0.4 cm, 0.5 cm, 0.6 cm or 0.7 cm.
[0108] In the present invention, the external magnetic field is preferably provided by a magnet; the magnetic field strength of the external magnetic field is preferably 0.01-0.5T, specifically 0.01T, 0.05T, 0.1T, 0.3T or 0.5T; the size of the magnet is preferably not less than the bottom size of the mold.
[0109] In the present invention, the compaction device is preferably a vibration table; the compaction time is preferably 3 to 5 minutes, specifically 3 minutes, 4 minutes or 5 minutes.
[0110] In the present invention, the curing preferably includes performing mold curing and demolding curing in sequence; the temperature of the mold curing is preferably 18-22°C, the humidity is preferably 95-98%, and the curing time is preferably 24-48h (the curing time is calculated from the completion of vibration).
[0111] In the present invention, the demoulding curing is preferably performed by soaking in a soaking liquid; the concentration of the soaking liquid is preferably 1 to 6M, specifically 1M, 3M, 5M or 6M; the soaking liquid preferably includes one or more of NaCl solution, KCl solution, Na2SO4 solution, K2SO4 solution, NaOH solution and KOH solution; the temperature of the demoulding curing is preferably room temperature. The present invention achieves better capacitance performance through soaking curing.
[0112] The present invention also provides the application of the structured electrode described in the above scheme or the structured electrode obtained by the preparation method described in the above scheme in the field of energy development and utilization.
[0113] The structural electrode provided by the present invention can be used in the field of energy development and utilization, specifically in energy utilization in the construction field or energy utilization in the civil engineering field, such as the foundation or partition wall of a building, to support the energy self-sufficiency of the building, promote the development of green energy buildings and energy self-sufficient buildings, and has a high market promotion value.
[0114] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0115] Example 1
[0116] This embodiment provides a method for a structural electrode having both energy storage capacity and compressive strength, using mineral powder, steel slag, sodium silicate, magnetic modified clay and graphene, and comprising the following steps:
[0117] (1) A total of 64 g of slag and steel slag were selected, dried at 105 °C for 24 h, and then ground in a planetary ball mill for 10 min to obtain slag powder and steel slag powder; silt clay was dried at 105 °C for 24 h, ground in a planetary ball mill at 16 rpm for 15 min, and 30 g of ground soil powder was obtained; 0.1 g of graphene was taken.
[0118] (2) Weigh 9.33 g of FeCl3·6H2O and 3.43 g of FeCl2·4H2O to ensure that Fe 3+ and Fe 2+ The molar ratio is 2:1; both of them are dissolved in 103.62g of deionized water to prepare a 0.5M iron salt solution.
[0119] (3) The iron salt solution prepared in step (2) is slowly added dropwise to a beaker containing a 10% NaOH solution under stirring, the pH value of the mixed solution is controlled between 9±0.3, stirred and heated to 70°C, and the coprecipitation reaction is continued for 30 minutes; then the Fe3O4 magnetic nanoparticles are separated from the solution using a centrifuge and repeatedly washed with deionized water until the pH value of the washing solution is 7.
[0120] (4) Add the activated clay into deionized water with a soil-water ratio of 1:5 to form a clay suspension.
[0121] (5) According to the mass ratio of clay to Fe3O4 magnetic nanoparticles of 1:0.5, Fe3O4 magnetic nanoparticles were added to the suspension of step (4) (the mass ratio of Fe3O4 magnetic nanoparticles to deionized water was 1:10), and stirred for 30 minutes. The mixture was then filtered, and the filtrate on the filter paper was placed in a drying oven, dried at 60°C to constant weight, and ground into fine powder to obtain magnetic modified clay.
[0122] (6) Slag powder, steel slag powder, magnetic modified clay, and graphene are mixed in a planetary ball mill for 30 seconds, and the mixture is placed in a stirring pot.
[0123] (7) Deionized water was weighed according to a water-cement ratio of 0.6, and the deionized water and the sodium silicate solution were poured into a stirring pot at the same time. The mixture was stirred for 3 minutes using a stirrer to obtain a uniform mixed slurry.
[0124] (8) The mixed slurry obtained in step (7) is injected into a 4 cm × 4 cm × 0.5 cm (side length × side length × thickness) mold, and the nickel foam is cut into 3.5 cm × 3.5 cm × 0.1 cm (side length × side length × thickness), and the nickel foam is immersed in the mixed slurry with good fluidity.
[0125] (9) The mold is placed on a vibration table, and a magnetic field is applied to both ends of the mold. The vibration table is turned on and vibrated for 3 minutes. The mold and the magnetic field are then placed in a curing room. After the mixed slurry hardens, the mold is removed and cured for 28 days to obtain a structured electrode.
[0126] Example 2
[0127] This embodiment provides a method for a structural electrode having both energy storage capacity and compressive strength, using mineral powder, steel slag, sodium silicate, magnetic modified clay and graphene, and comprising the following steps:
[0128] (1) A total of 64 g of slag and steel slag were selected, dried at 105 °C for 24 h, and then ground in a planetary ball mill for 10 min to obtain slag powder and steel slag powder; silt clay was dried at 105 °C for 24 h, ground in a planetary ball mill at 16 rpm for 15 min, and 30 g of ground soil powder was obtained.
[0129] (2) Weigh 9.33 g of FeCl3·6H2O and 3.43 g of FeCl2·4H2O to ensure that Fe 3+ and Fe 2+ The molar ratio is 2:1; both of them are dissolved in 103.62g of deionized water to prepare a 0.5M iron salt solution.
[0130] (3) The iron salt solution prepared in step (2) is slowly added dropwise to a beaker containing a 10% NaOH solution under stirring, and the pH value of the mixed solution is controlled to be 8; the mixture is stirred and heated to 80° C., and the coprecipitation reaction is continued for 30 minutes; the Fe3O4 magnetic nanoparticles are then separated from the solution using a centrifuge, and repeatedly washed with deionized water until the pH value of the washing solution is 8.
[0131] (4) Add the activated clay into deionized water with a soil-water ratio of 1:5 to form a clay suspension.
[0132] (5) According to the mass ratio of clay to Fe3O4 magnetic nanoparticles of 1:0.5, Fe3O4 magnetic nanoparticles were added to the suspension of step (4) (the mass ratio of Fe3O4 magnetic nanoparticles to deionized water was 1:10), and stirred for 30 minutes. The mixture was then filtered, and the filtrate on the filter paper was placed in a drying oven, dried at 60°C to constant weight, and ground into fine powder to obtain magnetic modified clay.
[0133] (6) Slag powder, steel slag powder and magnetic modified clay are mixed in a planetary ball mill for 30 seconds, and the mixture is placed in a stirring pot.
[0134] (7) Deionized water is weighed according to a water-cement ratio of 0.6, and 0.1 g of graphene is taken. The graphene is added to a beaker containing deionized water, and dispersed in an ultrasonic cleaner for 2 h to obtain a uniformly dispersed graphene dispersion; the graphene dispersion and the sodium silicate solution are poured into a stirring pot at the same time, and stirred with a stirrer for not less than 3 min until a uniform mixed slurry is obtained.
[0135] (8) Weigh 20 g of the mixed slurry obtained in step (7) and inject it into a 4 cm × 4 cm × 0.5 cm (side length × side length × thickness) mold. At the same time, cut the nickel foam to 3.5 cm × 3.5 cm × 0.1 cm (side length × side length × thickness) and immerse the nickel foam in the mixed slurry with good fluidity.
[0136] (9) The mold is placed on a vibration table, and a magnetic field is applied to both ends of the mold. The vibration table is turned on and vibrated for 3 minutes. The mold and the magnetic field are then placed in a curing room. After the mixed slurry hardens, the mold is removed and cured for 28 days to obtain a structured electrode.
[0137] Example 3
[0138] This embodiment provides a method for a structural electrode having both energy storage capacity and compressive strength, using mineral powder, steel slag, sodium silicate, magnetic modified clay and graphene, and comprising the following steps:
[0139] (1) A total of 64 g of slag and steel slag were selected, dried at 105 °C for 24 h, and then ground in a planetary ball mill for 10 min to obtain slag powder and steel slag powder; silt clay was dried at 105 °C for 24 h, ground in a planetary ball mill at 16 rpm for 15 min, and 30 g of ground soil powder was obtained.
[0140] (2) Weigh 9.33 g of FeCl3·6H2O and 3.43 g of FeCl2·4H2O to ensure that Fe 3+ and Fe 2+ The molar ratio is 2:1; both of them are dissolved in 103.62g of deionized water to prepare a 0.5M iron salt solution.
[0141] (3) The iron salt solution prepared in step (2) is slowly added dropwise to a beaker containing a 10% NaOH solution under stirring, the pH value of the solution is controlled to be 9, and the solution is stirred and heated to 75° C., and the coprecipitation reaction is continued for 30 minutes; then, the Fe3O4 magnetic nanoparticles are separated from the solution using a centrifuge and repeatedly washed with deionized water until the pH value of the washing solution is 7.
[0142] (4) Add the activated clay into deionized water with a soil-water ratio of 1:5 to form a clay suspension.
[0143] (5) According to the mass ratio of clay to Fe3O4 magnetic nanoparticles of 1:0.5, Fe3O4 magnetic nanoparticles were added to the suspension of step (4) (the mass ratio of Fe3O4 magnetic nanoparticles to deionized water was 1:10), and stirred for 30 minutes. The mixture was then filtered, and the filtrate on the filter paper was placed in a drying oven, dried at 60°C to constant weight, and ground into fine powder to obtain magnetic modified clay.
[0144] (6) Slag powder, steel slag powder and magnetic modified clay are mixed in a planetary ball mill for 30 seconds, and the mixture is placed in a stirring pot.
[0145] (7) Deionized water is weighed according to a water-cement ratio of 0.6, and 0.1 g of graphene is taken. The graphene is added to a beaker containing deionized water, and dispersed in an ultrasonic cleaner for 2 h to obtain a uniformly dispersed graphene dispersion; the graphene dispersion and the sodium silicate solution are poured into a stirring pot at the same time, and stirred with a stirrer for 3 min to obtain a uniform mixed slurry.
[0146] (8) Weigh 20 g of the mixed slurry obtained in step (7) and inject it into a 4 cm × 4 cm × 0.5 cm (side length × side length × thickness) mold. At the same time, cut the nickel foam to 3.5 cm × 3.5 cm × 0.1 cm (side length × side length × thickness) and immerse the nickel foam in the uniform slurry with good fluidity.
[0147] (9) The mold is placed on a vibration table, and a magnetic field is applied to both ends of the mold. The vibration table is turned on and vibrated for 3 minutes. The mold and the magnetic field are then placed in a curing room. After the mixed slurry hardens, the mold is removed and cured for 28 days to obtain a structured electrode.
[0148] Comparative Example 1
[0149] The structured electrode of this comparative example uses mineral powder, steel slag, sodium silicate, silty clay and graphene, and includes the following steps:
[0150] (1) A total of 64 g of slag and steel slag were selected, dried at 105°C for 24 h, and then ground in a planetary ball mill for 10 min to obtain slag powder and steel slag powder; silt clay was dried at 105°C for 24 h, crushed and ground, and passed through a 200-mesh sieve, and 30 g of the sieve was taken.
[0151] (2) Slag powder, steel slag powder and silt clay are mixed in a planetary ball mill for 30 seconds, and the mixture is placed in a stirring pot.
[0152] (3) Deionized water was weighed according to a water-cement ratio of 0.6, and 0.1 g of graphene was taken. The graphene was added to a beaker containing deionized water, and dispersed in an ultrasonic cleaner for 2 h to obtain a uniformly dispersed graphene dispersion; the graphene dispersion and the sodium silicate solution were poured into a stirring pot at the same time, and stirred with a stirrer for 3 min to obtain a uniform mixed slurry.
[0153] (4) Weigh 20 g of the mixed slurry obtained in step (3) and inject it into a mold. At the same time, cut the nickel foam into 3.5 cm×3.5 cm×0.1 cm (side length×side length×thickness) and immerse the nickel foam in the uniform slurry with good fluidity.
[0154] (5) The mold is placed on a vibration table and vibrated for 3 minutes. The mold is then placed in a curing room, and after the mixed slurry hardens, the mold is removed and cured for 28 days to obtain a structured electrode.
[0155] Comparative Example 2
[0156] The structured electrode of this comparative example uses mineral powder, steel slag, sodium silicate and graphene, and includes the following steps:
[0157] (1) A total of 64 g of slag and steel slag were selected, dried at 105 °C for 24 h, and then ground in a planetary ball mill for 10 min to obtain slag powder and steel slag powder, respectively.
[0158] (2) Mix slag powder and steel slag powder in a planetary ball mill for 30 seconds, and then put the mixture into a stirring pot.
[0159] (3) Deionized water was weighed according to a water-cement ratio of 0.6, and 0.1 g of graphene was taken. The graphene was added to a beaker containing deionized water, and dispersed in an ultrasonic cleaner for 2 h to obtain a uniformly dispersed graphene dispersion; the graphene dispersion and the sodium silicate solution were poured into a stirring pot at the same time, and stirred with a stirrer for 3 min to obtain a uniform mixed slurry.
[0160] (4) Weigh 20 g of the mixed slurry obtained in step (3) and inject it into a 4 cm × 4 cm × 0.5 cm (side length × side length × thickness) mold. At the same time, cut the nickel foam to 3.5 cm × 3.5 cm × 0.1 cm (side length × side length × thickness) and immerse the nickel foam in the uniform slurry with good fluidity.
[0161] (5) The mold is placed on a vibration table and vibrated for 3 minutes. The mold is then placed in a curing room. After the electrode is hardened, the mold is removed and cured for 28 days to obtain a structured electrode.
[0162] Comparative Example 3
[0163] The structured electrode of this comparative example is prepared from silicate cement (PO42.5), magnetic modified clay and graphene, comprising the following steps:
[0164] (1) Weigh 64 g of cement and silty clay, dry them at 105°C for 24 h, crush and grind them, and pass them through a 200-mesh sieve, taking 30 g of the sieve residue.
[0165] (2) Weigh 9.33 g of FeCl3·6H2O and 3.43 g of FeCl2·4H2O to ensure that Fe 3+ and Fe 2+ The molar ratio is 2:1; both of them are dissolved in 103.62g of deionized water to prepare a 0.5M iron salt solution.
[0166] (3) The iron salt solution prepared in step (2) was slowly added dropwise to a beaker containing a 10% NaOH solution under stirring, the pH value of the solution was controlled to 9, and the solution was stirred and heated to 70° C. for 30 min. The Fe3O4 magnetic nanoparticles were then separated from the solution using a centrifuge and repeatedly washed with deionized water until the pH value of the washing solution reached 8.
[0167] (4) The activated clay is added to deionized water with a soil-water ratio of 30:5 to form a clay suspension.
[0168] (5) According to the mass ratio of clay to Fe3O4 magnetic nanoparticles of 1:0.5, Fe3O4 magnetic nanoparticles were added to the suspension of step (4) (the mass ratio of Fe3O4 magnetic nanoparticles to deionized water was 1:10), and stirred for 30 minutes. The mixture was then filtered, and the filtrate on the filter paper was placed in a drying oven, dried at 60°C to constant weight, and ground into fine powder to obtain magnetic modified clay.
[0169] (6) Mix cement and magnetic modified clay in a planetary ball mill for 30 seconds, and then put the mixture into a mixing pot.
[0170] (7) Deionized water is weighed according to a water-cement ratio of 0.6, and 0.1 g of graphene is taken. The graphene is added to a beaker containing deionized water, and dispersed in an ultrasonic cleaner for 2 h to obtain a uniformly dispersed graphene dispersion; the graphene dispersion and the sodium silicate solution are poured into a stirring pot at the same time, and stirred with a stirrer for 3 min to obtain a uniform mixed slurry.
[0171] (8) Weigh 20 g of the mixed slurry obtained in step (7) and inject it into a 4 cm × 4 cm × 0.5 cm (side length × side length × thickness) mold. At the same time, cut the nickel foam to 3.5 cm × 3.5 cm × 0.1 cm (side length × side length × thickness) and immerse the nickel foam in the uniform slurry with good fluidity.
[0172] (9) The mold is placed on a vibration table, and a magnetic field is applied to both ends of the mold (so that the direction of the magnetic field is parallel to the surface of the nickel foam). The vibration table is turned on and vibrated for 3 minutes. The mold and the magnetic field are then placed in a curing room. After the mixed slurry hardens, the mold is removed and cured for 28 days to obtain a structured electrode.
[0173] The structured electrodes of Example 1 and Comparative Examples 1 to 3 were subjected to impedance spectroscopy test (EIS) and compressive strength test (CS) using a three-electrode system. The results are as follows: Figures 3-4 The surface capacitance of the structured electrodes of Example 1 and Comparative Examples 1 to 3 was statistically analyzed, and the results are as follows Figure 5 As shown. Figures 3 to 5 It can be seen that the ohmic internal resistance of the structured electrode prepared by industrial by-products is 7.2% lower than that of the cement sample (Comparative Example 3), and the surface capacitance is 327% of that of cement (Comparative Example 3), which is better than cement. The effect of the electrode prepared by magnetic modification of clay is better than that of unmodified clay, which shows that the structured electrode prepared by industrial by-product solidified magnetic modified soil has the potential for application in construction.
[0174] The cycle retention rate of the structured electrodes of Example 1 and Comparative Examples 1 to 3 was tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the structured electrode prepared by the present invention has a high cycle retention rate, and the cycle retention rate after 5000 times is above 93%.
[0175] It can be seen from the above embodiments that the structural electrode provided by the present invention has both load-bearing capacity and energy storage capacity, high cycle retention rate, high compressive strength, good stability, and good compatibility with buildings.
[0176] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An energy storage material, characterized in that: The energy storage carrying material comprises a matrix and a conductive network structure distributed inside the matrix; the matrix is a hydration product of industrial by-products; and the conductive network structure comprises conductive material and magnetic modified soil.
2. The energy storage material according to claim 1, characterized in that: The mass ratio of the matrix to the conductive network structure is 35-100:0.01-5; The mass ratio of the conductive material to the magnetic modified soil is 0.01-5:20-50.
3. The method for preparing the energy storage material according to any one of claims 1 to 2, characterized in that: The following steps are involved: The industrial by-product, magnetic modified soil, conductive material and alkaline activator are mixed to obtain a mixed slurry; the industrial by-product has pozzolanic activity and can undergo a pozzolanic reaction under a pH ≥ 10 environment; The mixed slurry is vibrated and cured in sequence in an external magnetic field to obtain the energy storage bearing material.
4. The preparation method according to claim 3, characterized in that: The magnetic modified soil is magnetic modified clay; the preparation method of the magnetic modified clay is: mixing the activated clay with water to obtain a clay suspension, adding Fe3O4 magnetic nanoparticles to the clay suspension, stirring and mixing, so that the clay particles in the clay suspension absorb the Fe3O4 magnetic nanoparticles; the Fe3O4 magnetic nanoparticles are composed of Fe 3+ and Fe 2+ The salts were synthesized by chemical co-precipitation.
5. A structural electrode, comprising an electrode body and a current collector partially embedded in the electrode body; the electrode body is the energy storage carrying material according to any one of claims 1 to 2 or the energy storage carrying material obtained by the preparation method according to any one of claims 3 to 4. 6 . The structural electrode according to claim 5 , wherein the length of the electrode body connection part on both sides of the current collector is the same as that of the electrode body, and the width is 0.3 to 0.7 cm.
7. The method for preparing the structured electrode according to any one of claims 5 to 6, characterized in that: The following steps are involved: The industrial byproduct, magnetic modified soil, conductive material and alkaline activator are mixed to obtain a mixed slurry; The mixed slurry is injected into a mold, and a current collector is placed into the mixed slurry while the mixed slurry is in a flowing state. The mold is then vibrated and cured in an external magnetic field to obtain the structured electrode.
8. The preparation method according to claim 7, characterized in that: The curing includes sequentially performing mold curing and demoulding curing; The temperature of the strip mold curing is 18-22° C., the humidity is 95-98%, and the curing time is 24-48 hours.
9. The preparation method according to claim 8, characterized in that: The demoulding curing comprises immersing in the immersion liquid; The concentration of the soaking liquid is 1-6M; the temperature of the demoulding curing is room temperature; The soaking solution includes one or more of NaCl solution, KCl solution, Na2SO4 solution, K2SO4 solution, NaOH solution and KOH solution.
10. Use of the structured electrode according to any one of claims 5 to 6 or the structured electrode prepared by the method according to any one of claims 7 to 9 in the field of energy development and utilization.